The Relationship between Happiness and Perceptions of Empowerment with Intention to Stay Working as a Registered Nurse in a University Hospital - Jaikhan, Krittaya; Sattayasomboon, Youwanuch; Sillabutra, Jutatip; Intaraprasong, Bhusita (Journal of Public Health Nursing, 2018)
Maintaining the nursing workforce in hospitals is a challenge to human resource management. This cross-sectional explanatory study examined the association between happiness and perceived empowerment with the intention to remain working as a registered nurse in a university hospital. A sample of 301 registered nurses (90.39%) who had worked at least 6 months were selected by stratified random sampling method. Data were collected using a selfadministered questionnaire which was valid and reliable (α > 0.8 ). Descriptive statistics were used to explain the variables. Pearson product-moment correlation and multiple liner regression were used to identify associated factors and predictors. The results showed that the intention to stay a university hospital nurse was at a high level (Mean = 3.55). Happiness and perceived empowerment were positive, significant factors associated with intention to stay but at a low level (r = 0.323 and 0.289, p-value < 0.001), and they were predictors that jointly explained 12.20% of the variance in the intention to stay a university hospital nurse (Adjusted R2 = 0.122, p-value < 0.001) In summary, this study recommends that nursing administrators may wish to increase means to promote happiness and perceived empowerment in retaining nursing staff.